A BioBrick™-Compatible Vector for Allelic Replacement Using the XylE Gene as Selection Marker. Issue 1 (December 2016) - Casanova, Michela; Pasotti, Lorenzo; Zucca, Susanna; Politi, Nicolò; Massaiu, Ilaria; Calvio, Cinzia; Cusella De Angelis, Maria; Magni, Paolo
Abstract Background Circular plasmid-mediated homologous recombination is commonly used for marker-less allelic replacement, exploiting the endogenous recombination machinery of the host. Common limitations of existing methods include high false positive rates due to mutations in counter-selection genes, and limited applicability to specific strains or growth media. Finally, solutions compatible with physical standards, such as the BioBrick™, are not currently available, although they proved to be successful in the design of other replicative or integrative plasmids. Findings We illustrate pBBknock, a novel BioBrick™-compatible vector for allelic replacement inEscherichia coli . It includes a temperature-sensitive replication origin and enables marker-less genome engineering via two homologous recombination events. Chloramphenicol resistance allows positive selection of clones after the first event, whereas a colorimetric assay based on thexylE gene provides a simple way to screen clones in which the second recombination event occurs. Here we successfully use pBBknock to delete the lactate dehydrogenase gene inE. coli W, a popular host used in metabolic engineering. Conclusions Compared with other plasmid-based solutions, pBBknock has a broader application range, not being limited to specific strains or media. We expect that pBBknock will represent a versatile solution both for practitioners, also among the iGEM competition teams, and for research laboratories that use BioBrick™-based assembly procedures.